2021
DOI: 10.1128/aac.01237-21
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of XAV-19, a Swine Glyco-humanized Polyclonal Anti-SARS-CoV-2 Antibody, for COVID-19-Related Moderate Pneumonia: a Randomized, Double-Blind, Placebo-Controlled, Phase IIa Study

Abstract: Objective: We assessed the pharmacokinetics and safety of XAV-19, a swine glyco-humanized polyclonal antibody against SARS-CoV-2, in COVID-19-related moderate pneumonia. To evaluate the optimal dose and safety of XAV-19 during this first administration to patients with COVID-19-related moderate pneumonia. Methods : In this phase 2a trial, adults with COVID-19-related moderate pneumonia of ≤10 days duration were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The supplementary data present the assessment of risk of bias of the included studies for each outcome. Twelve trials5054566065677286 proved at low risk of bias for all domains. All other studies proved at probably high or high risk of bias for at least one domain.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The supplementary data present the assessment of risk of bias of the included studies for each outcome. Twelve trials5054566065677286 proved at low risk of bias for all domains. All other studies proved at probably high or high risk of bias for at least one domain.…”
Section: Resultsmentioning
confidence: 97%
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, polyclonal antibodies produced in their Fab'2 format from horses 21 or in their IgG format from humanized cows 22 or glyco-humanized pigs 23 have also proven efficacy to neutralize SARS-CoV-2. The safety and tolerability in humans of Fab'2 from horses and of humanized IgG polyclonal antibodies has been confirmed recently in different clinical trials (Lopardo et al, 2021 21 , NCT04453384, NCT04469179, Gaborit et al, 2021 24 ), contrasting with unmodified polyclonal antibodies containing wild-type IgG antibodies that induce serum sickness and allergic reactions (including fever and skin rashes) in 20 to 30% of the patients, excepting for those who concomitantly receive immunosuppression and high doses steroids 25,26 . A partial efficacy of anti-SARS-CoV-2 Fab'2 from horses has been reported in those patients with negative baseline antibodies (NCT04494984).…”
Section: Introductionmentioning
confidence: 85%
“…Early after Covid-19 outbreak onset, many labs have been able to rapidly develop neutralizing antibodies. One year later, as of mid-2021, more than 93 clinical trials assessing the safety and benefit of mAbs and 8 of polyclonal antibodies are listed in the Clinicaltrials.gov repository ) estimated at 11.4 days24,46 . The data presented here, together with these pharmacokinetic data, indicate that XAV-19 can provide high and sustained therapeutic activity in vivo.…”
mentioning
confidence: 99%